Senior High School EFL Teacher and Students’ Use of Classroom Language: Penggunaan Bahasa Kelas oleh Guru dan Siswa Sekolah Menengah Atas EFL - Dewi, Isna Rafika; Anwar, Choiril (Universitas Muhammadiyah Sidoarjo, 2018)
This research was about the analysis of EFL teacher and students in using classroom language. The aim of this study was to find the errors in using classroom language. A descriptive research was used in this research. The samples of this research were an English teacher and science class students of a state senior high school. The researchers collected the data by using field note and voice recording. Then, the data findings were analyzed in using four steps. They are: identifying error, describing error, explaining error, and error evaluation. While data collection techniques were coding, revision, final coding, and result. From the result of the research, the researchers concluded that the errors found from respondents could be classified as local errors. It implies that those errors only affect a single element of sentence, but do not prevent a message from being hard.